Investigation into stable failure to short circuit in IGBT power modules - Yaqub, Imran (2015)
This doctoral thesis investigates modes of failure of the IGBT power module and how these modes can be coerced from an open circuit failure mode (OCFM) to a stable short circuit failure mode (SCFM) by using different interconnect technologies and material systems. SCFM is of great importance for a number of applications where IGBT power modules are connected in series string e.g. high voltage modular multi-level converters (M2LC) where one module failing to an OCFM can shut down the whole converter.